RESPONS OF LEKANG BABY TURTLES FED TUNA FISH VS. SHRIMP UP TO THREE MONTH OF AGE TO SUPPORT CONSERVATION - Sukada, I Ketut; Sumadi, I Ketut; Budaarsa, I Komang; Lanang Oka, I Gusti (E-Journal Of Animal Science Udayana University, 2012)
This research was carried out to study the response of lekang baby turtles or Day old Turtles (DOT) fed tuna fish compared to shrimp for three months from hatched. The result of the study hopefully might support their conversation since this species was reported as endanger species. Completely randomized design was used in this experiment using five feed treatments (A, B, C, D And E) which were 100% tuna, 75% tuna + 25% shrimp, 50% tuna + 50% shrimp, 25% tuna + 75% shrimp and 100% shrimp respectively. Statistical analysis showed that the average weight gain of baby turtles was significantly different among the all treatments where the fastest growth was showed by baby turtles fed 100% tuna (treatment A), while the slowest was the baby turtles in treatment E which were fed 100% shrimp. The baby turtles weight gains in treatment A, B, C, D and E were 0.79, 0.74, 0.63, 0.59, 0.52 g respectively. However, their feed consumption and feed conversion ratio mostly were not significantly different between the all treatments except for feed conversion ratio between treatment A and treatment E where baby turtles that fed 100% tuna more efficient than those fed 100% shrimp. This result was related to protein and energy consumption between the treatments and also related to protein and energy retention between those five treatments. The highest protein and energy consumption and also the protein and energy retention was shown by baby turtles fed 100% tuna and the lowest was shown by baby turtles by 100% shrimp. It was also found that width of the front flippers has close correlation with body weight (R2 = 0.74 and r = 0.86) of the baby turtles.  These flippers have an important function for swimming and diving because the baby turtles live in the sea. It might be concluded that lekang baby turtles grew faster up to three months old when were fed tuna fish compared to shrimp. Their efficiency in using feed for growth similar between the all feeding treatments. There was a close relationship between the size of flippers and body weight of lekang baby turtles. Therefore, management of lekang baby turtles by feeding them with tuna fish up to three months of age might support conservation program of the turtle particularly lekang turtle as endanger species in Indonesia.